2022
DOI: 10.1111/arcm.12820
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of strength, elasticity and rupture behaviour of birch tar made with ‘double‐pot’ techniques during tar cooking

Abstract: Birch tar was the first adhesive produced by humans. Its study has consequences for our understanding of human evolution and the development of specialised craftsmanship. One of the better-documented birch tar making methods is the 'double-pot' technique, where two containers are used, one containing bark, the other collecting the tar. Birch tar made with double-pots has low viscosity and bad adhesive properties. To obtain a usable adhesive, it must be reduced in volume by cooking. We investigate the evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…When mixed with fresh bitumen, 55 wt % ochre increases its strength by a factor of 3. Nonetheless, our values measured on fresh bitumen are very low if compared to lap-shear data reported on other archaeological adhesives [which fall in the range of τ u = 0.1 to 1.5 MPa (9,(62)(63)(64)]. We therefore attempted to identify other possible performance gains of a high ochre load in bitumen.…”
Section: Experimental Testing Of the Ochre-bitumen Mixturementioning
confidence: 77%
“…When mixed with fresh bitumen, 55 wt % ochre increases its strength by a factor of 3. Nonetheless, our values measured on fresh bitumen are very low if compared to lap-shear data reported on other archaeological adhesives [which fall in the range of τ u = 0.1 to 1.5 MPa (9,(62)(63)(64)]. We therefore attempted to identify other possible performance gains of a high ochre load in bitumen.…”
Section: Experimental Testing Of the Ochre-bitumen Mixturementioning
confidence: 77%
“…The comparison of our values with theirs might be slightly offset, as they used wooden laps and we aluminium laps. However, this offset is only minimal, as shown by a recent comparison of wooden and aluminium laps for birch tar lap-shear testing (Schmidt et al 2022a). This study found aluminium laps to produce slightly higher overall strength values than wooden laps, suggesting that an offset of 30% (for τ (yield) ) or 15% (for τ u ) should be applied when comparing values produced with both types of lap materials.…”
Section: Comparison Of Our Data With Previous Birch Tar Lap-shear Testsmentioning
confidence: 98%
“…It has previously been argued that tar made with double-pot distillation might require further cooking to thicken it and make it more usable (Schenk and Groom 2018). A recent study has shown that cooking time has an effect on the adhesive properties of tar (Schmidt et al 2022a). For our experiments, we decided to let the raised structure cool overnight to let the tar thicken naturally.…”
Section: Birch Tar Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors note that degradation and potential re-heating of tar could have an unknown influence on the chemical signatures. A recent study showed that adhesive strength can be increased through post-production re-heating of birch tar [ 46 ], but chemical alteration during such processes, as well as a way of recognising them in archaeological contexts, has not yet been assessed. Consequently, it is not only the lack of direct archaeological data on the production method, but also any post-production processing, such as reheating or mixing, that we do not fully understand yet.…”
Section: Introductionmentioning
confidence: 99%